Sewing room accessories - Shore, Debbie . (Tunbridge Wells, Kent [England] : Search Press Ltd, 2017)
The latest addition to the Love to Sew series, this new title from best-selling author Debbie Shore contains 15 gorgeous, practical items that every sewer will love to make, use or give as gifts. The book contains storage solutions and sewing accessories to equip every sewing space. The projects range from practical storage solutions such as tool rolls, carry cases and cutting mat carriers to innovative ways to keep a sewing space tidy, such as a handy armchair storage device and an ironing station, complete with board cover and handy hanging pouch for storing a mini iron and attachments. The book also contains colourful sewing room essentials such as a pincushion, a seam press and handmade bobbins, and inspiring items perfect to give as gifts: a sewing room diary cover and a sewing case. The book contains a comprehensive materials and techniques section at the beginning, showing clearly all the techniques needed, with beautiful photography and easy-to-follow instructions. Each of the projects contains step-by-step photography and clear instructions so that even beginners will find these projects a doddle.
Introduction 6Materials and Equipment 8Basic Techniques 12Projects:Pumpkin pincushion 16Fabric bobbins 20Sewing case 22Machine cover and mat 26Tidy caddy 28Cutting mat carrier 32Sewing circle 34Tool roll 36Chair storage 40Seam press 44Ironing station 46Sewing machine cover 50Pin and pattern pouch 54Sewing diary cover 56Carry case 60
Keywords: Sewing -- Equipment and supplies; Notions (Merchandise)